New Innovation of "Pancasila and Rahmatan lil Alamin Student Profiles" in Indonesia: Why Does Islamic Education Need It? - Sadam Fajar Shodiq (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
Pancasila is the foundation of Indonesia's national ideology, which promotes unity in diversity and harmonious relations between different religions and cultures. This article aimed to explore the development of nationalism-religious character through the project to strengthen Pancasila student and Rahmatan lil Alamin profiles. This research utilizes a literature review approach to examine the existing literature on the role of religion in developing national identity and character, as well as the importance of Pancasila in Indonesian society. The research also analyzes the current state of education in Indonesia, with a focus on the potential of the education system to promote nationalism-religious character development. The research findings suggest that integrating religious and nationalism values into the education system can help promote nationalism-religious character development among students. The project to strengthen Pancasila and Rahmatan lil Alamin student profiles in Indonesia can contribute to this effort by instilling in students a sense of responsibility towards their country and their fellow citizens. In conclusion, developing nationalism-religious character through the project to strengthen Pancasila and Rahmatan lil Alamin student profiles in Indonesian Islamic educational institutions is crucial for promoting national identity, peace, and countering radicalism. By integrating Pancasila values and fostering religious tolerance, these institutions can shape students into responsible citizens who uphold national values and contribute to the harmonious development of society. Challenges such as curriculum integration, teacher training, and community engagement must be addressed to ensure the successful implementation of this project. Further research is recommended to assess this initiative's long-term effects and sustainability in achieving its intended outcomes.